Regulation of Dense-Core Granule Replenishment by Autocrine BMP Signalling in Drosophila Secondary Cells. - Siamak Redhai; Josephine E E U Hellberg; Mark Wainwright; Sumeth W Perera; Felix Castellanos; Benjamin Kroeger; Carina Gandy; Aaron Leiblich; Laura Corrigan; Thomas Hilton; Benjamin Patel; Shih-Jung Fan; et al. (PLoS Genetics)
Regulated secretion by glands and neurons involves release of signalling molecules and enzymes selectively concentrated in dense-core granules (DCGs). Although we understand how many secretagogues stimulate DCG release, how DCG biogenesis is then accelerated to replenish the DCG pool remains poorly characterised. Here we demonstrate that each prostate-like secondary cell (SC) in the paired adult Drosophila melanogaster male accessory glands contains approximately ten large DCGs, which are loaded with the Bone Morphogenetic Protein (BMP) ligand Decapentaplegic (Dpp). These DCGs can be marked in living tissue by a glycophosphatidylinositol (GPI) lipid-anchored form of GFP. In virgin males, BMP signalling is sporadically activated by constitutive DCG secretion. Upon mating, approximately four DCGs are typically released immediately, increasing BMP signalling, primarily via an autocrine mechanism. Using inducible knockdown specifically in adult SCs, we show that secretion requires the Soluble NSF Attachment Protein, SNAP24. Furthermore, mating-dependent BMP signalling not only promotes cell growth, but is also necessary to accelerate biogenesis of new DCGs, restoring DCG number within 24 h. Our analysis therefore reveals an autocrine BMP-mediated feedback mechanism for matching DCG release to replenishment as secretion rates fluctuate, and might explain why in other disease-relevant systems, like pancreatic β-cells, BMP signalling is also implicated in the control of secretion.